HDAC4 depletion ameliorates IL‐13‐triggered inflammatory response and mucus production in nasal epithelial cells via activation of SIRT1/NF‐κB signaling. Issue 11 (11th October 2022) - Xu, Hangyu; Wang, Lingjun; Chen, Huaqun; Cai, Hefei
Abstract: Introduction: Allergic rhinitis (AR) is frequently known as a chronic respiratory disease with a global high prevalence. The pivotal roles of histone deacetylase 4 (HDAC4) in multiple human diseases have been underlined by numerous studies. Nevertheless, whether HDAC4 is implicated in AR remains to be elaborated. The objective of the current study is to clarify the impacts of HDAC4 on AR. Methods: First, human nasal epithelial cells (hNECs) were pretreated by interleukin‐13 (IL‐13). HDAC4 expression in hNECs with the presence or absence of IL‐13 treatment was tested by quantitative reverse‐transcription polymerase chain reaction (RT‐qPCR) and western blot. Following, after HDAC4 was depleted, levels of histamine, Immunoglobulin E (IgE) and inflammatory factors were analyzed by ELISA assay. Then, Mucin‐5AC (MUC5AC) expression was examined through RT‐qPCR, western blot, and IF assay. Western blot was to analyze the expression of sirtuin 1 (SIRT1)/nuclear factor‐kappaB (NF‐κB) signaling‐related proteins. After IL‐13‐induced hNECs were cotransfected with HDAC4 interference plasmids and SIRT1 inhibitor EX527, the functional experiments above were conducted again. Results: The experimental data in this study presented that HDAC4 expression was increased in IL‐13‐induced hNECs. Silencing of HDAC4 cut down the levels of histamine, IgE and inflammatory factors and the expression of MUC5AC. Additionally, knockdown of HDAC4 led to the activation of SIRT1/NF‐κB signaling. Further, the downregulated levels of histamine, IgE and inflammatory factors and the expression of MUC5AC imposed by HDAC4 interference were all reversed by EX527. Conclusions: In short, HDAC4 inhibition activated SIRT1/NF‐κB signaling to mitigate inflammatory response and mucus production in IL‐13‐treated nasal epithelial cells in AR. Abstract : Allergic rhinitis (AR) is frequently known as a chronic respiratory disease with global high prevalence. The pivotal roles of histone deacetylase 4 (HDAC4) in multiple human diseases have been underlined by numerous studies. Our paper is the first to explore the role of HDAC4 in AR and the mechanism involved. We concluded that HDAC4 inhibition activated SIRT1/NF‐κB signaling to mitigate inflammatory response and mucus production in interleukin‐13‐treated nasal epithelial cells in AR.